Aggregated planning in the broiler chicken industry: a case study in Santa Marta (Colombia) (2019)
The poultry meat market requires a careful coordination of the broiler chicken supply chain. We study the case of a medium-sized company that focuses mainly in farm and slaughtering operations for broiler chicken production. For this company, lot sizing and scheduling are critical tasks for an efficient operation of their business. We present a framework of decision support models that could help similar companies in the broiler chicken industry to become more competitive.